Analisis Pengaruh Anggaran Berbasis Kinerja, Sistem Akuntansi Keuangan Daerah, Dan Sistem Informasi Pengelolaan Keuangan Terhadap Penilaian Kinerja Bud Pada Bppkad Kabupaten Ponorogo - anshori, farida (Universitas Slamet Riyadi, 2020)
The results of the calculations showed that multiple linear regression using the t test showed that the performance-based budgeting system had a significant significant effect on the performance of BPPKAD Ponorogo District office employees, so that hypothesis 1, which reads Performance Based Budgeting System, had a significant effect on the performance of BPPKAD employees. Multiple linear regression using the t test shows that the Financial Accounting system has a significant effect on the performance of BPPKAD Ponorogo Regency employees, so that hypothesis 2 that reads the Financial Accounting System has a significant effect on the performance of the Ponorogo Regency BPPKAD office staff, is proven to be true. Multiple linear regression using the t test shows the influence of financial management information systems on the performance of BPPKAD Ponorogo Regency employees statistically significant, so that hypothesis 3 is proven to be true.Â Keywords: Performance Based Budgeting, Regional Financial Accounting, Systems Financial Management Information Systems, Performance Appraisa